MALATHION INDUCED CHANGES IN LACTATE DEHYDROGENASE ISOENZYMES OF RED MUSCLE OF Heteropneustes fossilis (BLOCH) - NILESH, KUMAR; DURGA, BHOWMICK (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Malathion, an organophosphate pesticide, is generally used in crop fields to reduce the loss of farm produce. However, its concomitant run-off from agricultural fields poses major threat to the aquatic fauna and especially fishes are exposed to such toxicity causing changes in various biochemical parameters involved in different metabolic pathways. The five isoenzymes of LDH identified electrophoretically, show conspicuous changes in terms of number and quantity with respect to different concentrations and exposure periods of malathion.